Nanotheranostics for Diagnosis and Treatment of Breast Cancer - Patel, Parth; Kumar, Kishore; Jain, Vineet K.; Popli, Harvinder; Yadav, Awesh K.; Jain, Keerti (Current Pharmaceutical Design, 2023)
Recently, breast cancer has reached the highest incident rate amongst all the reported cancers, and one of its variants, known as triple-negative breast cancer (TNBC), is deadlier compared to the other types of breast cancer due to a lack of feasible diagnostic techniques. Advancements in nanotechnology have paved the way to formulate several nanocarriers with the ability to deliver anticancer drugs effectively and selectively to cancer cells with minimum side effects to non-cancerous cells. Nanotheranostics is a novel approach that can be used in the diagnosis of disease along with therapeutic effects. Currently, various imaging agents, such as organic dyes, radioactive agents, upconversion nanoparticles, various contrasting agents, quantum dots, etc., are being explored for the imaging of internal organs or to examine drug distribution. Furthermore, ligand-targeted nanocarriers, which have the potential to target cancer sites, are being used as advanced agents for cancer theranostic applications, including the identification of various metastatic sites of the cancerous tumor. This review article discusses the need for theranostic application in breast cancer with various imaging techniques, the latest nanotheranostic carriers in breast cancer, and related safety and toxicity issues, as well as highlights the importance of nanotheranostics in breast cancer, which could be helpful in deciphering questions related to nanotheranostic systems.
Keywords: nanotheranostic formulations